1992
DOI: 10.1038/358587a0
|View full text |Cite
|
Sign up to set email alerts
|

Homodimer formation of retinoid X receptor induced by 9-cis retinoic acid

Abstract: Retinoid response pathways are mediated by two classes of receptors, the retinoic acid receptors (RARs) and the retinoid X receptors (RXRs). A central question is whether distinct response pathways are regulated by these two classes of receptors. The observation that the stereoisomer 9-cis-retinoic acid binds with high affinity to RXRs suggested that this retinoid has a distinct role in controlling RXR activity, but it was almost simultaneously discovered that RXRs function as auxiliary receptors for RARs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

25
409
2
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 571 publications
(437 citation statements)
references
References 29 publications
25
409
2
1
Order By: Relevance
“…By overexpressing RARa and phosphorylation-defective RARaS77A in parallel in either RARa mutant or RARaÀ/À cells, we along with others have found that RARaS77A, but not RARa, inhibits proliferation and induces differentiation in either normal or cancer cells (Taneja et al, 1997;Rochette-Egly et al, 2000;Crowe and Kim, 2002;Luo et al, 2007;Wang et al, 2009). RA-bound RARs and/or RXRs function as transcription factors to induce transactivation by modulating protein-DNA interactions at the RA responsive element (RARE) in the promoters of target genes (Mangelsdorf et al, 1991;Zhang et al, 1992;Chambon, 1996), although the underlying mechanisms remain to be dissected.…”
Section: Introductionmentioning
confidence: 79%
“…By overexpressing RARa and phosphorylation-defective RARaS77A in parallel in either RARa mutant or RARaÀ/À cells, we along with others have found that RARaS77A, but not RARa, inhibits proliferation and induces differentiation in either normal or cancer cells (Taneja et al, 1997;Rochette-Egly et al, 2000;Crowe and Kim, 2002;Luo et al, 2007;Wang et al, 2009). RA-bound RARs and/or RXRs function as transcription factors to induce transactivation by modulating protein-DNA interactions at the RA responsive element (RARE) in the promoters of target genes (Mangelsdorf et al, 1991;Zhang et al, 1992;Chambon, 1996), although the underlying mechanisms remain to be dissected.…”
Section: Introductionmentioning
confidence: 79%
“…While retinoid-dependent transactivation by RXR is mediated in part by RXR homodimers (66), RXR is also able to form heterodimers with TR and VDR (7,18,36,37,46,48,64,65). In each case, target gene binding by the nuclear hormone receptor is greatly enhanced by its partnership with RXR.…”
mentioning
confidence: 96%
“…First, we performed transient transfections in JEG-3 cells, which express low levels of endogenous RARs. A CAT reporter gene containing the palindromic (inverted repeat) element TREp, which can be activated by both RARs and RXRs (47,66), was used. Figure 2A shows that as expected, RA and 9-cis RA activated transcription by both RARs and RXRs (38,44,47,66).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of RA, retinoid receptors can function in the form of either RAR-RXR heterodimers or RXR-RXR homodimers [10]. In addition, RXR can form heterodimers with various other members of the steroid/thyroid/retinoid receptor family, including nur77 [11].…”
Section: Introductionmentioning
confidence: 99%